2003
DOI: 10.1086/375637
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Glycine

Abstract: We have searched for interstellar conformer I glycine (NH 2 CH 2 COOH), the simplest amino acid, in the hot molecular cores Sgr B2(N-LMH), Orion KL, and W51 e1/e2. An improved search strategy for intrinsically weak molecular lines, involving multisource observations, has been developed and implemented. In total, 82 spectral frequency bands, in the millimeter-wave region, were observed over a 4 yr period; 27 glycine lines were detected in 19 different spectral bands in one or more sources. The rotational temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
389
4
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(412 citation statements)
references
References 57 publications
18
389
4
1
Order By: Relevance
“…In these objects icy mantles have sublimated. For over two decades, COMs have been detected only in massive hot cores, while recently they have also been observed in three hot corinos, lowmass star-forming regions (Cazaux et al 2003;Kuan et al 2004;Bottinelli et al 2004a,b). Because hot corinos have sizes of a few tens of AU, the size of the solar nebula, it is particularly relevant to study the COMs formation and destruction mechanism because of the link to the formation of the Solar System.…”
Section: Introductionmentioning
confidence: 99%
“…In these objects icy mantles have sublimated. For over two decades, COMs have been detected only in massive hot cores, while recently they have also been observed in three hot corinos, lowmass star-forming regions (Cazaux et al 2003;Kuan et al 2004;Bottinelli et al 2004a,b). Because hot corinos have sizes of a few tens of AU, the size of the solar nebula, it is particularly relevant to study the COMs formation and destruction mechanism because of the link to the formation of the Solar System.…”
Section: Introductionmentioning
confidence: 99%
“…We looked for HCNO in several positions in SgrB2 associated with hot or warm environments, where HOCN had previously been detected (see Brünken et al 2010), while HOCN was searched for in the cold to lukewarm dense cores observed in Marcelino et al (2009). We have also included in our search the well-studied low-mass protostar IRAS 16293-2422, where HNCO has been found to be prominent (Bisschop et al 2008), and a rich organic chemistry has been widely observed as a result of mantle grain desorption and, possibly, warm gas chemistry (see, e.g., Cazaux et al 2003;Kuan et al 2004;Garrod & Herbst 2006;Garrod et al 2008, and references therein). The observed positions are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, this search also failed, in a similar way to successive searches toward Sgr B2(N-LMH) and OMC1 (Hollis et al 2003a,b). In the same year, hopes were raised by the claim of glycine detection in three high-mass star-formation regions, Sgr B2(N-LMH), Orion KL, and W51 (Kuan et al 2003). However, it was first disputed (Snyder et al 2005) and finally rejected four years later Cunningham et al 2007).…”
Section: Introductionmentioning
confidence: 99%